2022
DOI: 10.3390/ijms23137154
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Sex Hormones: Crosstalking Players in Cardiometabolic and Cardiovascular Disease

Abstract: The available evidence indicates a close connection between gut microbiota (GM) disturbance and increased risk of cardiometabolic (CM) disorders and cardiovascular (CV) disease. One major objective of this narrative review is to discuss the key contribution of dietary regimen in determining the GM biodiversity and the implications of GM dysbiosis for the overall health of the CV system. In particular, emerging molecular pathways are presented, linking microbiota-derived signals to the local activation of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 171 publications
0
19
0
1
Order By: Relevance
“…Estrogen, progesterone and testosterone, are the major decisive factors of sex differences in mammals [33]. Studies have shown that sex hormones generally influence the composition of the sex-specific gut microbiota by regulating intestinal homeostasis in the following ways [34][35][36]: (i) direct gene expression regulation in intestinal epithelial cells by binding with specific nuclear steroid hormone receptor (SHR) transcription factors; (ii) participation in the TLR pathway to change the inflammatory immune environment; and (iii) the activity of orphan nuclear estrogen-related receptor α (ESRRA) in mitochondrial function. In agreement, α-diversity was significantly different between the sexes only among postpubescent mice [37].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen, progesterone and testosterone, are the major decisive factors of sex differences in mammals [33]. Studies have shown that sex hormones generally influence the composition of the sex-specific gut microbiota by regulating intestinal homeostasis in the following ways [34][35][36]: (i) direct gene expression regulation in intestinal epithelial cells by binding with specific nuclear steroid hormone receptor (SHR) transcription factors; (ii) participation in the TLR pathway to change the inflammatory immune environment; and (iii) the activity of orphan nuclear estrogen-related receptor α (ESRRA) in mitochondrial function. In agreement, α-diversity was significantly different between the sexes only among postpubescent mice [37].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary derivatives of these compounds include red meat, liver, fish, dairy products, and eggs, whereas sources of betaine (a choline oxidation product) also include wheat bran, wheat germ, and spinach ( Senthong et al, 2016 ). Intestinal bacterial strains with trimethylamine lyases convert these nutritional substrates to trimethylamine ( Maffei et al, 2022 ). Trimethylamine from the gut reaches the liver by portal circulation, where host hepatic FMO3 incorporates oxygen atoms into trimethylamine to form TMAO ( Gątarek and Kałużna-Czaplińska, 2021 ).…”
Section: Tmao Physiological and Pathophysiological Actionsmentioning
confidence: 99%
“…As discussed above, TMAO induces activation of the NF-kB resulting in the generation of proinflammatory cytokines that contribute to atherogenesis and vascular injury and remodelling ( Seldin et al, 2016 ). TMAO also upregulates the nod-like receptor family pyrin domain containing 3 (NLRP3) inflammasome formation ( Chen et al, 2017 ), and increases serum levels of the proinflammatory lipopolysaccharide (LPS) endotoxin ( Maffei et al, 2022 ). NLRP3 Inflammasome leads to increased production of inflammatory cytokines and this has been demonstrated in carotid artery endothelial cells (CAECs), human aortic endothelial cells (HAECs) and vascular smooth muscle cells (VSMCs) suggesting that NLRP3 initiates an endothelial inflammatory response cascade leading to endothelial dysfunction ( Seldin et al, 2016 ; Boini et al, 2017 ).…”
Section: Tmao and Hypertension Mechanismsmentioning
confidence: 99%
“…The compositional and functional disequilibrium of the gut ecosystem, known as dysbiosis, is accountable for the disclosure of several diseases from neurological affections [ 130 , 131 ], to the liver [ 132 ], cardiovascular [ 133 ], autoimmune diseases [ 134 ], food allergies [ 135 ], diabetes [ 136 ], obesity [ 137 ], cancer development [ 138 ], decreased calcium absorption [ 139 ], and even influence the severity of infectious disease such as COVID-19 [ 140 , 141 ]. The applicability of these compounds can exert an alleged “prebiotic” outcome on the health of humans and animals.…”
Section: Health Benefits Of Pegsmentioning
confidence: 99%